The Evolution of Cloud Computing : How to Plan for Change. - Longbottom, Clive (BCS Learning & Development Limited, 2017)
Cloud computing has been positioned as today's ideal IT platform. This book looks at what cloud promises and how it's likely to evolve in the future. Readers will be able to ensure that decisions made now will hold them in good stead in the future and will gain an understanding of how cloud can deliver the best outcome for their organisations.